Validation of the Chinese Western Ontario and McMaster Universities Osteoarthritis Index in Patients From Mainland China With Osteoarthritis of the Knee. Issue 11 (November 2015) - Symonds, Tara; Hughes, Bernadette; Liao, Shanmei; Ang, Qiuqing; Bellamy, Nicholas
Abstract : Objective: To establish the reliability, validity, and sensitivity to change of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) among Chinese subjects with osteoarthritis (OA) of the knee, living in mainland China. Methods: A multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group study was conducted for validation of the electronic personal digital assistant version of the WOMAC Numerical Rating Scale (NRS) 3.1 Index in China. A total of 287 subjects with OA of the knee were randomized to receive either meloxicam (15 mg) or placebo. Psychometric properties of the WOMAC were evaluated by estimating the reliability, validity, and sensitivity to change. Equivalence of the electronic version was also compared with the paper version. Results: Intraclass correlation coefficients for the WOMAC pain, stiffness, and physical function subscales were 0.81, 0.76, and 0.85, respectively, indicating good test–retest reliability. Similarly, internal consistency was strong (Cronbach's alpha for the 3 WOMAC subscales was 0.84, 0.86, and 0.96, respectively). Pearson's correlation coefficients for WOMAC pain and Short Form 36 health survey (SF‐36) bodily pain, as well as WOMAC physical function and SF‐36 physical functioning domains were >0.4, indicating convergent validity, whereas the coefficients for all 3 WOMAC domains with SF‐36 mental health and mental health component scores were <0.4, indicating divergent validity. There was strong discriminant validity between healthy volunteers and OA patients. The effect sizes of change from baseline to week 12 in WOMAC subscale scores were large, demonstrating sensitivity to change. Equivalence between paper and electronic versions was very high. Conclusion: The culturally and linguistically validated Chinese version of the WOMAC NRS 3.1 for mainland China is psychometrically robust in its validity, reliability, and sensitivity to change for patients with OA of the knee.